Pengaruh Motivasi Intrinsik Dan Ekstrinsik Terhadap Kinerja Karyawan Pada Perusahaan Purwanto Farm (Studi Pada Perusahaan Purwanto Farm) - Sholikhin, Ahmad; Pardiman, Pardiman; Sholehuddin, Sulton (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to analyze the effect of intrinsic motivation and extrinsic motivation on employee performance at Purwanto Farm Blitar. The research data were obtained through a survey by distributing questionnaires to 30 employees using a Non-Probability Sampling technique. Data analysis was conducted using a quantitative method with the assistance of SPSS version 27. The results showed that intrinsic motivation did not have a positive and significant effect on employee performance, whereas extrinsic motivation had a partially positive and significant effect on employee performance. Based on the findings, it is recommended that the company focus more on aspects of extrinsic motivation, such as providing rewards, compensation, salaries and benefits, good working conditions, job security, and supervision from superiors to improve overall employee performance. Keywords: Intrinsic Motivation, Extrinsic Motivation, Employee Performance